Retrospective Analysis of the Treatment Outcome in Myeloid Leukemia of Down Syndrome in Polish Pediatric Leukemia and Lymphoma Study Group From 2005 to 2019 - Malgorzata Czogala; Malgorzata Czogala; Katarzyna Pawinska-Wasikowska; Katarzyna Pawinska-Wasikowska; Teofila Ksiazek; Teofila Ksiazek; Barbara Sikorska-Fic; Michal Matysiak; Jolanta Skalska-Sadowska; Jacek Wachowiak; Anna Rodziewicz-Konarska; Alicja Chybicka; et al. (Frontiers Media S.A., 2020)
Background: Children with Down syndrome (DS) have increased risk of myeloid leukemia (ML), but specific treatment protocols ensure excellent outcome. This study was a retrospective analysis of the treatment results and genetic characteristics of ML of DS (ML-DS) in Poland from 2005 to 2019.Methods: All 54 patients with ML-DS registered in the Polish Pediatric Leukemia and Lymphoma Study Group in analyzed period were enrolled to the study. There were 34 children treated with Acute Myeloid Leukemia-Berlin-Frankfurt-Munster 2004 Interim Protocol (group I) and 20 patients treated with ML-DS 2006 Protocol (group II). In the first protocol, there was reduction of the antracyclines doses and intrathecal treatment for ML-DS compared to non-DS patients. In the second protocol, further reduction of the treatment was introduced (omission of etoposide in the last cycle, no maintenance therapy).Results: Probabilities of 5-year overall survival (OS), event-free survival (EFS), and relapse-free survival in the whole analyzed group were 0.85 ± 0.05, 0.83 ± 0.05, and 0.97 ± 0.03, respectively. No significant differences were found between two protocols in the terms of OS and EFS (0.79 ± 0.07 vs. 0.95 ± 0.05, p = 0.14, and 0.76 ± 0.07 vs. 0.95 ± 0.05, p = 0.12, respectively). All deaths were caused by the treatment-related toxicities. Reduction of the treatment-related mortality was noticed (20% in group I and 5% in group II). The only one relapse in the whole cohort occurred in the patient from group I, older than 4 years, without GATA1 gene mutation. He was treated successfully with IdaFLA cycle followed by hematopoietic stem cell transplantation from matched sibling donor. No significant prognostic factor was found in the study group probably due to low number of patients in the subgroups.Conclusions: The study confirms that the reduced intensity protocols are very effective in ML-DS patients. The only cause of deaths was toxicities; however, systematic decrease of the treatment-related mortality was noticed.